Bioactive glass doped with noble metal nanoparticles for bone regeneration: in vitro kinetics and proliferative impact on human bone cell line. Issue 41 (25th July 2021) - Mostafa, Amany A.; El-Sayed, Mayyada M. H.; Emam, Ahmed N.; Abd-Rabou, Ahmed A.; Dawood, Reham M.; Oudadesse, Hassane
Abstract : This work investigates the bioactivity of novel silver-doped (BG-Ag) and gold-doped (BG-Au) quaternary 46S6 bioactive glasses synthesized via a semi-solid-state technique. Abstract : This work investigates the bioactivity of novel silver-doped (BG-Ag) and gold-doped (BG-Au) quaternary 46S6 bioactive glasses synthesized via a semi-solid-state technique. A pseudo-second-order kinetic model successfully predicted the in vitro uptake kinetic profiles of the initial ion-exchange release of Ca in simulated body fluid, the subsequent Si release, and finally, the adsorption of Ca and P onto the bioactive glasses. Doping with silver nanoparticles enhanced the rate of P uptake by up to approximately 90%; whereas doping with gold nanoparticles improved Ca and P uptake rates by up to about 7 and 2 times, respectively; as well as Ca uptake capacity by up to about 19%. The results revealed that the combined effect of Ca and Si release, and possibly the release of silver and gold ions into solution, influenced apatite formation due to their effect on Ca and P uptake rate and capacity. In general, gold-doped bioactive glasses are favoured for enhancing Ca and P uptake rates in addition to Ca uptake capacity. However, silver-doped bioactive glasses being less expensive can be utilized for applications targeting rapid healing. In vitro studies showed that BG, BG-Ag and BG-Au had no cytotoxic effects on osteosarcoma MG-63 cells, while they exhibited a remarkable cell proliferation even at low concentration. The prepared bioactive glass doped with noble metal nanoparticles could be potentially used in bone regeneration applications.